The Effect of Compensation and Work Discipline on Employee Performance: Study At a Telephone Company Located in Bandung - Nurhabibah, Fauziah; Riadi, Farid; Adinata, Ujang Wawan Sam; Adang, Adang (Acman: Accounting and Management Journal, 2023)
The primary objective of this study is to comprehensively examine and assess the impact of Compensation and Work Discipline on Employee Performance in the context of the Covid-19 Pandemic, with a specific focus on a telecommunications company located in Bandung. The research methodology employed in this study is path analysis, which examines the relationship between employee performance and factors such as Compensation and Work Discipline. Path analysis also helps elucidate the interconnectedness among the predetermined variables under investigation. According to the study's findings, the level of employee compensation at the telephone company in Bandung is transitioning from a low to a moderately good level. Similarly, the work discipline of the employees is also experiencing a shift from a low to a moderately good level. The impact of compensation and work discipline on employee performance at the telephone company in Bandung is a subject of general interest. The Compensation variable demonstrates a partial influence of 9.4% on Employee Performance, whereas the joint impact of Compensation and Work Discipline on Employee Performance is significant at 62.7%. The findings of the conducted research indicate that these factors substantially impact the performance of employees at the telecommunications company located in Bandung.